Leadership Development Using Three Modes of Educational Delivery: Online, Blended and Face to Face - Ladyshewsky, Rick; Taplin, Ross (Association for the Advancement of Computing in Education, 2014)
This research explores differences in the development of life long learning skills that support leadership development across three different modes of educational delivery. Performance outcomes from 550 students across three modes of educational delivery in a post graduate leadership and management course were compared. The 12 module course and the two projects that learners were responsible for completing were the same across the three modes of delivery. Delivery mode included face to face, blended and fully online. Students in the fully online mode did significantly better in their two projects in comparison to students in the face to face and blended mode. For the first project, female students did significantly better than males in the face to face mode, and insignificantly less well than males in the blended and fully online mode. This research suggests that the development of life-long learning skills that support leadership development can occur using a range of delivery modes, including fully online. The importance of collaboration appears to have some bearing on female student performance and suggests this is an important variable to consider in course design, particularly as it moves to more virtual means. The ability to use fully online, blended and face to face delivery methods to develop life-long learning skills that support leadership development is encouraging given the highly humanistic orientation of this subject matter and its historical tendency to be delivered in face to face formats. Organisations that purchase and deliver leadership development programs might consider expanding delivery options to meet the needs of busy leaders given the results of this research.